The Effect of Project-Based Learning on Students' Creativity, Learning Motivation, and Critical Thinking Skills - Herlin Erawati; Lilik Sri Hariani; Sulistyo Sulistyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Education plays an important role in preparing students to face the challenges of the 21st century that demand critical, creative, and adaptive thinking skills. This study analyzes the effect of the Project Based Learning (PjBL) model on creativity, learning motivation, and critical thinking skills of students in the Social Studies subject at the junior high school level. The method used is a quantitative approach with a Quasi Experimental Nonequivalent Control Group Design. The research subjects consisted of two classes, namely the experimental group of 32 students who received project-based learning, and the control group of 33 students who learned through conventional methods. The instruments in the form of questionnaires and observations were analyzed using the Independent Sample T-Test to compare the results before and after treatment. The results showed that PjBL had a significant effect on increasing creativity, learning motivation, and critical thinking skills with a significance value of 0.000. This model is able to create contextual, collaborative learning experiences, and demands active student involvement in solving real problems.